TERRITORIAL MARKETING WITH VIRTUAL TOURS: AN EFFECTIVE STRATEGY FOR PROMOTING TERRITORY - Yasser Nassim Benzagouta; Imane Fantazi; Meriem Seghiri; Abdelaziz Debbache; Insaf Boumezbeur (International Journal of Innovative Technologies in Social Science, 2024)
Essentially, the attractiveness of a territory seems to be linked to its ability to attract flows and make itself desirable. We then speak of attraction, or more precisely, appeal, which refers not only to demographic, environmental, and economic dimensions but also to criteria of notoriety, image, and reputation. In this sense, the tourism sector appears to be a vital lever for the competitiveness of a territory. Due to its ability to generate visibility and readability of spaces and vernacular products, this sector is often seen as a first experimentation of a city or country, leading to a possible retention of visitors. The literature review often describes Algeria as an extremely attractive territory, while other indicators point to a rather unappealing image of the country. We will then make the distinction between attractiveness, which first refers to the presence of potential, and competitiveness, which rather addresses the management of this capital. The challenge thus seems to be oriented towards the implementation of a logic that allows taking advantage of the assets present in situ to better respond to this problem of capturing and satisfying demand, both nationally and internationally. However, this issue must be addressed with up-to-date data. It must take into account the evolution of tourists’ behavior, who increasingly refer to digital media to outline an image of their future destinations. Thus, the digital age and the growing importance of information and communication technologies seem to be revolutionizing territorial marketing and, in particular, the tourism sector. Naturally, the reflection turns to Algeria’s ability to accompany this movement. In other words, what are the methods and tools used in terms of territorial marketing and, more precisely, in the field of tourism and e-tourism? Our research undertakes a retrospective of experiences with virtual tours of heritage monuments produced by our team (using a 3D scanner). From the Bey’s palace to the tomb of Massinissa, passing through the Roman aqueduct of Constantine, we attempt to highlight the impact of these innovative tourism products in enhancing the tourist elements of a city or territory. An introspection of the feedback on these services will allow us to better understand the expectations of visitors on one side, and to revise territorial marketing approaches on the other. The objective is to move away from classical policies by proposing more competitive, innovative strategies.